Implementasi Peraturan Menteri Pendidikan Nasional Republik Indonesia Nomor 25 Tahun 2008 Tentang Standar Tenaga Perpustakaan di SMA Negeri 3 Kayu Agung Kabupaten Ogan Komering Ilir - Erlinda Erlinda; Mega Nugraha; Sunarto Sunarto (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Erlinda, Implementation of the Regulation of the Minister of National Education of the Republic of Indonesia Number 25 of 2008 concerning Library Personnel Standards at SMA Negeri 3 Kayu Agung, Ogan Komering Ilir Regency.This research is included in the type of qualitative research. Data collection techniques are carried out by observation, interviews, and documentation studies. The data analysis technique was carried out by analyzing the data of an interactive model from Miles and Huberman. Research results: 1) Communication has not gone well, so the results achieved are not optimal. In the future, it is hoped that there will be better communication and coordination, so that every problem that occurs is related to the implementation of Permendiknas RI No. 25 of 2008; 2) The intensity of training that is not too routine plus the competence of less qualified employees causes the training provided to have less effect on work achievement; 3) The implementation of Permendiknas RI No. 25 of 2008 concerning Library Personnel Standards at SMA Negeri 3 Kayuagung already has a clear operating system (SOP) standard; 4) In implementing policies, all policy implementers have a high commitment, and as much as possible will work with full dedication and responsibility for the achievement of the desired goals, as stated in Permendiknas RI No. 25 of 2008 concerning Manpower Standards The library.